Eliminating inter-ethnic inequalities? Impacts of education policies on ethnic minority children in Vietnam - Huyen Chi, T (2011)
Based on the Young Lives survey in 2006 and a qualitative research on 23 Kinh (the majority), Hmong and H'Roi children from the Young Lives sample in Lao Cai and Phu Yen provinces in 2008, this paper discusses the mixed impact of the implementation of education policies aimed at ethnic minorities in Vietnam. The paper finds that, despite a conspicuous expansion in access to basic education for ethnic minority students, the majority-minority gap in educational achievement persists. Case studies suggest that an uneven allocation of resources partly accounts for the varying record of performance across regions, i.e., between lowlanders and highlanders, and between those who are the direct beneficiaries of socio-development aid and those who are not. Access to quality education by the ethnic minority students is further undermined by poor administration and some examples of corruption on the one hand, and the lack of parental and community participation and scrutiny on the other. Children's experiences in education and development programmes, presented in their own voices, mirror their place in the existing structure of inequality in the society. As intended beneficiaries, children are not only aware, but are also critical evaluators, of programmes run in their name. A full understanding of the sources of marginalisation in education therefore necessitates in-depth longitudinal studies of children's experiences of poverty in the context of local and national political economy. The paper ends with a call for a genuine effort of policymakers, local authorities and other stakeholders in education and development not only to listen to children's voices but also to incorporate their concerns and hopes to effect meaningful change.